Method for improving conductivity and anti-sticking property of aluminum alloy resistance spot welding electrode

By adding graphene and tungsten carbide powder to aluminum alloy resistance spot welding electrodes, a multilayer composite electrode material is formed, which solves the problems of electrode deformation and adhesion under high temperature and high pressure, improves wear resistance and conductivity, and extends electrode life.

CN120901444AActive Publication Date: 2025-11-07CHANGCHUN SANYOU AUTOMOTIVE PARTS MFG CO LTD
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511447399.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-11
Publication Date
2025-11-07
Estimated Expiration
2045-10-11

AI Technical Summary

Technical Problem

Existing aluminum alloy resistance spot welding electrodes are prone to deformation, wear, and adhesion under high temperature and high pressure, resulting in unstable weld quality. Furthermore, existing improvement methods often reduce conductivity or cause coating peeling.

Method used

A mixture of copper-chromium-zirconium alloy powder, graphene powder, and tungsten carbide powder is used to form an electrode end face layer, a transition layer, and an electrode substrate through vacuum ball milling. The mixture is then subjected to hot pressing sintering and reverse extrusion forming to create a multilayer composite electrode material.

Benefits of technology

It improves the wear resistance and anti-adhesion performance of the electrodes, extends the electrode life, maintains high conductivity, and increases the number of consecutive spot welding cycles by more than 35%.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120901444A_ABST
    Figure CN120901444A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of welding and connection, and relates to a method for improving conductivity and anti-sticking property of an aluminum alloy resistance spot welding electrode, which comprises the following steps: preparing three areas of an electrode end surface layer, a transition layer and an electrode substrate, and then carrying out integral hot pressing sintering and backward extrusion forming to prepare a composite electrode material. The tungsten carbide is added to improve the wear-resistant and anti-sticking performance of the end face of the electrode, and the graphene is added to improve the conductivity of the electrode; a transition layer is arranged between the electrode substrate and the end surface layer so as to reduce the thermal stress fatigue of the electrode; through backward extrusion process forming, the electrode composite material after hot pressing sintering can be further compacted, the bonding strength of a composite electrode material interface is improved, the dispersion distribution state of graphene in a copper-chromium-zirconium matrix is improved, and the uniformity and conductivity of the material are improved. Compared with a conventional chromium-zirconium-copper electrode, the method has the advantages that the wear resistance of the electrode can be improved by more than 30%, the electric conductivity is improved by about 10%, and the number of continuous spot welding times of the electrode in the spot welding process of the aluminum alloy is increased by more than 35%.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The application belongs to the technical field of welding and connection, and particularly relates to a method capable of effectively improving the conductivity and anti-adhesion capacity of an aluminum alloy resistance spot welding electrode. BACKGROUND

[0002] Resistance spot welding is a key connection technology in the production process of automobile structural parts. Specifically, under the condition of applying pressure, resistance spot welding uses the resistance heat generated by the current passing through the contact surface and the adjacent area of the connection joint to heat it to a local melting or plastic melting state, so that it forms a metal bond. Resistance spot welding has been widely used in the automobile, aviation, electronics and other industries due to its reliable quality, high efficiency, good economy and easy automation.

[0003] In the field of new energy vehicles, the use of aluminum alloy body structural parts has become an important direction for the development of vehicle lightweight. However, due to the small resistivity and large thermal conductivity of aluminum alloy, a large current is required during spot welding, resulting in high energy consumption. In actual production and processing, there are still many problems: 1. The existing spot welding electrode materials are usually copper-chromium-zirconium, chromium-bronze, tungsten-copper and other copper alloy materials. Under the coupling effect of high temperature and high pressure, the electrode end surface is prone to thermal deformation and wear; 2. Copper and aluminum can easily form low-melting-point eutectic compounds, which can cause corrosion and adhesion of the aluminum alloy plate and the copper alloy electrode end surface under high temperature and high pressure. Deformation, wear and adhesion of the electrode can seriously affect the current distribution state of the electrode and the workpiece contact surface area, reducing the quality stability of the welding spot.

[0004] In recent years, the annual production of complete vehicles in China has reached 300 million, and each complete vehicle body has about 4000-5000 spot welding connections. Due to the problem of electrode wear and adhesion, the conventional chromium-zirconium-copper electrode needs to be ground and polished after about 30-40 spot welding of aluminum alloy plates, resulting in a loss of more than 100 tons of spot welding electrode material, which greatly affects production efficiency and cost. In order to improve the high-temperature deformation resistance, wear resistance and adhesion resistance of the electrode, existing literature has proposed methods such as adding ceramic particles to the electrode matrix or laser cladding and spraying hard materials on the electrode surface. Although adding ceramic particles and hard alloys can improve the strength of the electrode material, the existence of interfaces and defects between different phases of the material will inevitably lead to a decrease in the conductivity of the electrode, causing the electrode to heat up during high-current spot welding and easily softening and plastically deforming under high temperature and high pressure. The methods of laser cladding or spraying hard materials can easily cause problems such as coating peeling and thermal stress, reducing the service life of the electrode. Therefore, how to improve the wear resistance and adhesion resistance of the electrode material without reducing the conductivity of the electrode, and prolong the service life of the electrode, is still a problem that needs to be solved in the production and manufacturing of aluminum alloy structural parts resistance spot welding. SUMMARY

[0005] The purpose of the present application is to provide a method for improving the conductivity and anti-sticking property of aluminum alloy resistance spot welding electrodes, to effectively improve the conductivity and anti-sticking ability of spot welding electrodes during aluminum alloy resistance spot welding, thereby improving the spot welding quality and extending the service life of the electrodes.

[0006] The purpose of the present application is achieved by the following technical solutions: A method for improving the conductivity and anti-sticking property of aluminum alloy resistance spot welding electrodes, comprising the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder; according to wt.% by mass percentage: the graphene powder is 0.5-1.2%, the tungsten carbide powder is 15-60%, and the balance is copper-chromium-zirconium alloy powder, vacuum ball milling for 2h, to obtain the wear-resistant and anti-sticking electrode end face layer material powder P1; S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder; according to wt.% by mass percentage: the graphene powder is 0.2-0.6%, the tungsten carbide powder is 5-20%, and the balance is copper-chromium-zirconium alloy powder, vacuum ball milling for 2h, to obtain the electrode transition layer material powder P2; S13, preparation of electrode base material powder P3: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder; according to wt.% by mass percentage: the graphene powder is 0.1-0.2%, and the balance is copper-chromium-zirconium alloy powder, vacuum ball milling for 2h, to obtain the high-conductivity electrode base material powder P3; S2, overall hot pressing and sintering: The electrode end face layer material powder P1 is loaded into the hot pressing mold, loaded at room temperature at 200-600MPa, and the powder is vibrated and compacted to form a wear-resistant and anti-sticking electrode end face layer blank; the upper mold ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot pressing mold, the ram is pressed down, and the powder is vibrated and compacted at 200-600MPa to form a superposition of the electrode end face layer blank and the transition layer blank; the upper mold ram is raised, the electrode base material powder P3 is continuously loaded into the hot pressing mold, the ram is pressed down, and the powder is vibrated and compacted at 200-600MPa to form a multi-layer superposition of the electrode end face layer blank, the transition layer blank and the electrode base blank; the thickness of the electrode end face layer is 1-2mm, and the thickness of the transition layer is 1-2mm; After the multi-layer blank is pressed, the multi-layer electrode base is generated by integral hot-press sintering under the protection of argon; wherein, the sintering temperature is 850-1050 DEG C, specifically 900 DEG C, the pressure load is 80-150 MPa, specifically 120 MPa, the sintering time is 60-120 min, specifically 60 min, and the temperature in the furnace after sintering is 400-650 DEG C, specifically 650 DEG C; S3, backward extrusion forming: The hot-press sintered multi-layer electrode base and the hot-press mold are taken out from the hot-press sintering furnace, the hot-press mold press head is replaced with a backward extrusion mold press head, and the backward extrusion forming is carried out in a press machine, the backward extrusion forming temperature is 400-650 DEG C, specifically 650 DEG C, the pressing rate is 0.05-2 mm / s, specifically 0.1 mm / s, the electrode cap outer diameter is 20 mm after backward extrusion forming, the total height is 15 mm, and the composite electrode material meeting the size requirements of the composite spot welding is obtained after finishing; wherein, in the hot-press sintering and backward extrusion deformation processes, a mold design of one mold with multiple pieces can be used.

[0007] Further, in step S11, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, the particle size of the graphene powder is less than 0.1 um, and the particle size of the tungsten carbide powder is less than 10 um.

[0008] Further, in step S12, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, the particle size of the graphene powder is less than 0.1 um, and the particle size of the tungsten carbide powder is 10 um.

[0009] Further, in step S13, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, and the particle size of the graphene powder is less than 0.1 um.

[0010] Further, in step S2, the powder is vibrationally compacted under a load of 300 MPa at room temperature.

[0011] Further, in step S2, after compaction, the thicknesses of the electrode base, the transition layer and the electrode end surface layer are 6 mm, 2 mm and 1 mm respectively.

[0012] Further, in step S2, the sintering temperature is 900 DEG C, the pressure load is 120 MPa, the sintering time is specifically 60 min, and the temperature in the furnace after sintering is 650 DEG C.

[0013] Compared with the prior art, the beneficial effects of the present application are: The method adds graphene powder and tungsten carbide powder into copper-chromium-zirconium alloy powder, hot-presses and sinter to form a composite electrode material, which comprises an electrode end surface layer, a transition layer and an electrode substrate, and the component proportions of the three regions are different. BRIEF DESCRIPTION OF DRAWINGS

[0014] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following will briefly introduce the drawings needed to be used in the embodiments. It should be understood that the following drawings only show some of the embodiments of the present application, and therefore should not be regarded as a limitation to the scope, and for those skilled in the art, other related drawings can also be obtained without creative labor.

[0015] Figure 1 The step flow chart of the method for improving the conductivity and anti-sticking property of the aluminum alloy resistance spot welding electrode; Figure 2 The microstructure between the electrode substrate and the transition layer in the composite electrode material; Figure 3 The microstructure between the transition layer and the end surface layer in the composite electrode material. DETAILED DESCRIPTION

[0016] The present application will be further described below in conjunction with the embodiments: The present application will be further described below in conjunction with the embodiments:

[0017] It should be noted that: similar labels and letters represent similar items in the following drawings, therefore, once an item is defined in one drawing, it does not need to be further defined and explained in the subsequent drawings. Meanwhile, in the description of the present application, the terms "first", "second" and the like are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0018] The application provides a method for improving the conductivity and anti-sticking property of an aluminum alloy resistance spot welding electrode. Figure 1 As shown in the figure, the preparation method specifically comprises the following steps: S1, preparation of electrode material powder: The electrode material powder is divided into three types: electrode end face layer material powder P1, electrode transition layer material powder P2 and electrode base material powder P3, and the specific preparation method is as follows: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, the tungsten carbide powder with a particle size of less than 10 um is screened, and the mass percentage wt.% is 0.5-1.2% for the graphene powder, 15-60% for the tungsten carbide powder, and the balance for the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 hours to obtain the wear-resistant and anti-sticking electrode end face layer material powder P1 for standby.

[0019] S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, the tungsten carbide powder with a particle size of 10 um is screened, and the mass percentage wt.% is 0.2-0.6% for the graphene powder, 5-20% for the tungsten carbide powder, and the balance for the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 hours to obtain the electrode transition layer material powder P2 for standby.

[0020] S13, preparation of electrode base material powder P3: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer graphene powder with a particle size of less than 0.1 um is selected, and the mass percentage wt.% is 0.1-0.2% for the graphene powder and the balance for the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 hours to obtain the high-conductivity electrode base material powder P3 for standby.

[0021] S2, overall hot-press sintering: The electrode end surface layer material powder P1 is loaded into the hot-pressing mold, a load of 200-600 MPa, specifically 300 MPa, is applied at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end surface layer blank; the upper mold ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 200-600 MPa, specifically 300 MPa, to form a superposition of the electrode end surface layer blank and the transition layer blank; the upper mold ram is raised, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 200-600 MPa, specifically 300 MPa, to form a multi-layer superposition of the electrode end surface layer blank, the transition layer blank, and the electrode base blank. The thickness of the electrode end surface layer is 1-2 mm, and the thickness of the transition layer is 1-2 mm. Specifically, after compaction, the thicknesses of the electrode base, the transition layer, and the electrode end surface layer are 6 mm, 2 mm, and 1 mm, respectively.

[0022] After the multi-layer blank is pressed together, overall hot-press sintering is performed under argon protection to generate a multi-layer electrode base. The sintering temperature is 850-1050°C, specifically 900°C, the pressure load is 80-150 MPa, specifically 120 MPa, the sintering time is 60-120 min, specifically 60 min, and after sintering is completed, the temperature in the furnace is maintained at 400-650°C, specifically 650°C.

[0023] S3, reverse extrusion forming: The multi-layer electrode base sintered by hot-pressing is removed from the hot-press sintering furnace, the hot-pressing mold ram is replaced with a reverse extrusion mold ram, and the reverse extrusion forming is performed in a press machine. The reverse extrusion forming temperature is 400-650°C, specifically 650°C, and the ram pressing rate is 0.05-2 mm / s, specifically 0.1 mm / s. After reverse extrusion forming, the electrode cap has an outer diameter of 20 mm and a total height of 15 mm, and after finishing, a composite electrode material that meets the size requirements of composite spot welding is obtained. In the hot-press sintering and reverse extrusion deformation processes, a mold design of one mold with multiple pieces can be used.

[0024] The high electrical conductivity and wear-resistant and anti-adhesion performance of the composite electrode material are achieved in the following ways: 1. The electrode base region is prepared by adding graphene powder to a copper-chromium-zirconium alloy to maintain high electrical conductivity. 2. Tungsten carbide is added to the electrode end surface layer region to improve the wear-resistant and anti-adhesion performance of the electrode end surface. Since tungsten carbide has good hardness and wear resistance and low affinity with aluminum, it can reduce the adhesion and erosion of the electrode end surface during aluminum alloy spot welding. Graphene powder is added to the electrode end surface layer to prevent a decrease in electrode conductivity caused by the addition of tungsten carbide. 3. A transition layer is added between the electrode end surface layer and the electrode base to alleviate thermal stress fatigue caused by temperature cycling of the electrode during spot welding, since the thermal expansion coefficients of tungsten carbide and copper-chromium-zirconium are different, and the mass fraction of tungsten carbide in the transition layer is less than that in the end surface layer; 4. After the powders in different regions of the composite electrode material are hot-pressed and sintered together, the hot-pressed and sintered composite electrode material is further compacted through a reverse extrusion process, so as to improve the bonding strength of the internal interfaces of the material, and further improve the dispersion distribution of graphene in the copper-chromium-zirconium alloy and the uniformity and conductivity of the electrode material.

[0025] Embodiment 1 A method for improving the conductivity and anti-sticking property of an aluminum alloy resistance spot welding electrode, comprising the following steps: S1. Preparation of electrode material powder: S11. Preparation of electrode end surface layer material powder P1: The electrode end surface layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um, and the tungsten carbide powder with a particle size of less than 10 um are selected, and the mass percentage is wt. %: 0.6% of graphene powder, 40% of tungsten carbide powder, and the balance of copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the wear-resistant and anti-adhesion electrode end surface layer material powder P1 for standby.

[0026] S12. Preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um, and the tungsten carbide powder with a particle size of 10 um are selected, and the mass percentage is wt. %: 0.3% of graphene powder, 20% of tungsten carbide powder, and the balance of copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the electrode transition layer material powder P2 for standby.

[0027] S13. Preparation of electrode base material powder P3: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um and the few-layer graphene powder with a particle size of less than 0.1 um are selected, and the mass percentage is wt. %: 0.1% of graphene powder, and the balance of copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the high-conductivity electrode base material powder P3 for standby.

[0028] S2. Overall hot-pressing and sintering: The electrode end surface layer material powder P1 is loaded into the hot pressing die, a load of 300 MPa is applied at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end surface layer blank; the upper die ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot pressing die, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a superposition of the electrode end surface layer blank and the transition layer blank; the upper die ram is raised, the electrode base material powder P3 is continuously loaded into the hot pressing die, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a multi-layer superposition of the electrode end surface layer blank, the transition layer blank, and the electrode base blank. After compaction, the thicknesses of the electrode base, the transition layer, and the electrode end surface layer are 6 mm, 2 mm, and 1 mm, respectively.

[0029] After the multi-layer blank is pressed, overall hot pressing sintering is performed under argon protection to generate a multi-layer electrode base. The sintering temperature is 900°C, the pressing load is 120 MPa, the sintering time is 60 min, and the temperature in the furnace is 650°C after sintering is completed.

[0030] S3, reverse extrusion forming: The multi-layer electrode base sintered by hot pressing is taken out of the hot pressing sintering furnace, the hot pressing die ram is replaced with a reverse extrusion die ram, and the reverse extrusion forming is performed in a press machine. The reverse extrusion forming temperature is 650°C, and the ram down rate is 0.1 mm / s. After reverse extrusion forming, the electrode cap has an outer diameter of 20 mm and a total height of 15 mm. After finishing, a composite electrode material that meets the size requirements of composite spot welding is obtained.

[0031] Example 2: A method for improving the conductivity and anti-adhesion of an aluminum alloy resistance spot welding electrode includes the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end surface layer material powder P1: The electrode end surface layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder, and tungsten carbide powder. The copper-chromium-zirconium alloy powder has a particle size of 20-50 um, the few-layer nanoscale graphene powder has a particle size of less than 0.1 um, and the tungsten carbide powder has a particle size of less than 10 um. The mass percentage is wt. %: 1.2% of graphene powder, 30% of tungsten carbide powder, and the balance of copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the wear-resistant and anti-adhesion electrode end surface layer material powder P1, which is ready for use.

[0032] S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, and the tungsten carbide powder with a particle size of 10 um is screened. According to the mass percentage, the graphene powder is 0.6%, the tungsten carbide powder is 15%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the electrode transition layer material powder P2 for standby.

[0033] S13, electrode base material powder P3 preparation: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, and the few-layer graphene powder with a particle size of less than 0.1 um is selected. According to the mass percentage, the graphene powder is 0.2%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the high-conductivity electrode base material powder P3 for standby.

[0034] S2, overall hot-pressing sintering: The electrode end surface layer material powder P1 is loaded into a hot-pressing mold, a load of 300 MPa is applied at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end surface layer blank; the upper mold ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a superposition of the electrode end surface layer blank and the transition layer blank; the upper mold ram is raised, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a multi-layer superposition of the electrode end surface layer blank, the transition layer blank and the electrode base blank. After compaction, the thicknesses of the electrode base, the transition layer and the electrode end surface layer are 6 mm, 2 mm and 1 mm, respectively.

[0035] After the multi-layer blank is pressed, overall hot-pressing sintering is performed under argon protection to generate a multi-layer electrode base. The sintering temperature is 900°C, the pressing load is 120 MPa, the sintering time is 60 min, and the furnace is kept at 650°C after sintering is completed.

[0036] S3, reverse extrusion forming: The hot-pressing sintered multi-layer electrode base and the hot-pressing mold are taken out of the hot-pressing sintering furnace, the hot-pressing mold ram is replaced with a reverse extrusion mold ram, and the reverse extrusion forming is performed in a press at a temperature of 650°C and a pressing rate of 0.1 mm / s. After reverse extrusion forming, the electrode cap has an outer diameter of 20 mm and a total height of 15 mm. After finishing, the composite spot welding size required composite electrode material is obtained.

[0037] Example 3: A method for improving the conductivity and anti-sticking property of an aluminum alloy resistance spot welding electrode, comprising the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, and the tungsten carbide powder with a particle size of less than 10 um is screened. According to the mass percentage wt.%, the graphene powder is 0.5%, the tungsten carbide powder is 20%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the wear-resistant and anti-adhesion electrode end face layer material powder P1 for standby.

[0038] S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, and the tungsten carbide powder with a particle size of 10 um is screened. According to the mass percentage wt.%, the graphene powder is 0.2%, the tungsten carbide powder is 10%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the electrode transition layer material powder P2 for standby.

[0039] S13, preparation of electrode base material powder P3: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, and the few-layer graphene powder with a particle size of less than 0.1 um is selected. According to the mass percentage wt.%, the graphene powder is 0.1%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling for 2 h obtains the high-conductivity electrode base material powder P3 for standby.

[0040] S2, overall hot-pressing sintering: The electrode end face layer material powder P1 is loaded into a hot-pressing mold, a load of 300 MPa is applied at room temperature, the powder is vibrated and compacted to form a wear-resistant and anti-adhesion electrode end face layer blank; the upper mold press head is raised, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the press head is pressed down, and the powder is vibrated and compacted at 300 MPa to form a superposition of the electrode end face layer blank and the transition layer blank; the upper mold press head is raised, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the press head is pressed down, and the powder is vibrated and compacted at 300 MPa to form a multi-layer superposition of the electrode end face layer blank, the transition layer blank and the electrode base blank. After compaction, the thicknesses of the electrode base, the transition layer and the electrode end face layer are 6 mm, 2 mm and 1 mm, respectively.

[0041] After the multi-layer blank is pressed, the whole hot-press sintering is carried out under the protection of argon to generate the multi-layer electrode matrix. The sintering temperature is 900 DEG C, the pressure load is 120 MPa, the sintering time is 60 min, and the furnace is kept at 650 DEG C after sintering.

[0042] S3, backward extrusion forming: The hot-press sintered multi-layer electrode matrix and the hot-press mold are taken out of the hot-press sintering furnace, the hot-press mold pressure head is replaced with a backward extrusion mold pressure head, and the backward extrusion forming is carried out in a pressure machine. The backward extrusion forming temperature is 650 DEG C, and the pressing rate is 0.1 mm / s. After backward extrusion forming, the electrode cap outer diameter is 20 mm, and the total height is 15 mm. After finishing, the composite spot welding size required composite electrode material is obtained.

[0043] Example 4: A method for improving the conductivity and anti-sticking of aluminum alloy resistance spot welding electrode, comprising the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed by copper chromium zirconium alloy powder, graphene powder and tungsten carbide powder. The copper chromium zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, the tungsten carbide powder with a particle size of less than 10 um is screened, and the mass percentage is wt.%: the graphene powder is 0.5%, the tungsten carbide powder is 20%, and the balance is the copper chromium zirconium alloy powder. Vacuum ball milling for 2h obtains the wear-resistant and anti-adhesion electrode end face layer material powder P1 for standby.

[0044] S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed by copper chromium zirconium alloy powder, graphene powder and tungsten carbide powder. The copper chromium zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, the tungsten carbide powder with a particle size of 10 um is screened, and the mass percentage is wt.%: the graphene powder is 0.2%, the tungsten carbide powder is 10%, and the balance is the copper chromium zirconium alloy powder. Vacuum ball milling for 2h obtains the electrode transition layer material powder P2 for standby.

[0045] S13, preparation of electrode matrix material powder P3: The electrode matrix material powder P3 is mixed by copper chromium zirconium alloy powder and graphene powder. The copper chromium zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer graphene powder with a particle size of less than 0.1 um is selected, and the mass percentage is wt.%: the graphene powder is 0.1%, and the balance is the copper chromium zirconium alloy powder. Vacuum ball milling for 2h obtains the high-conductivity electrode matrix material powder P3 for standby.

[0046] S2, whole hot-pressing sintering: The electrode end face layer material powder P1 is loaded into the hot-pressing mold, a load of 300 MPa is loaded at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end face layer blank; the upper mold ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a superposition of the electrode end face layer blank and the transition layer blank; the upper mold ram is raised, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a multi-layer superposition of the electrode end face layer blank, the transition layer blank, and the electrode base blank. After compaction, the thicknesses of the electrode base, the transition layer, and the electrode end face layer are 6 mm, 2 mm, and 1 mm, respectively.

[0047] After the multi-layer blank is pressed, whole hot-pressing sintering is performed under argon protection to generate a multi-layer electrode base. The sintering temperature is 900°C, the pressing load is 120 MPa, the sintering time is 60 min, and the furnace is kept at 650°C after sintering is completed.

[0048] S3, reverse extrusion forming: The hot-pressing sintered multi-layer electrode base and the hot-pressing mold are taken out of the hot-pressing sintering furnace, the hot-pressing mold ram is replaced with a reverse extrusion mold ram, and the reverse extrusion forming is performed in a press machine. The reverse extrusion forming temperature is 650°C, and the pressing rate is 0.1 mm / s. After reverse extrusion forming, the electrode cap has an outer diameter of 20 mm and a total height of 15 mm. After finishing, a composite electrode material that meets the size requirements of composite spot welding is obtained.

[0049] Example 5: A method for improving the conductivity and anti-adhesion of an aluminum alloy resistance spot welding electrode includes the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder, and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nanoscale graphene powder with a particle size of less than 0.1 um is selected, and the tungsten carbide powder with a particle size of less than 10 um is screened. The mass percentage is wt. %: 0.8% of graphene powder, 15% of tungsten carbide powder, and the balance of copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the wear-resistant and anti-adhesion electrode end face layer material powder P1, which is ready for use.

[0050] S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed by copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, the few-layer nano graphene powder with a particle size of less than 0.1 um is selected, and the tungsten carbide powder with a particle size of 10 um is screened. According to the mass percentage, the wt.% of the graphene powder is 0.5%, the wt.% of the tungsten carbide powder is 5%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the electrode transition layer material powder P2 for standby.

[0051] S13, electrode base material powder P3 preparation: The electrode base material powder P3 is mixed by copper-chromium-zirconium alloy powder and graphene powder. The copper-chromium-zirconium alloy powder with a particle size of 20-50 um is selected, and the few-layer graphene powder with a particle size of less than 0.1 um is selected. According to the mass percentage, the wt.% of the graphene powder is 0.2%, and the balance is the copper-chromium-zirconium alloy powder. Vacuum ball milling is performed for 2 h to obtain the high-conductivity electrode base material powder P3 for standby.

[0052] S2, overall hot-pressing sintering: The electrode end surface layer material powder P1 is loaded into a hot-pressing mold, a load of 300 MPa is applied at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end surface layer blank; the upper mold ram is raised, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a superposition of the electrode end surface layer blank and the transition layer blank; the upper mold ram is raised, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the ram is pressed down, and the powder is vibrationally compacted at 300 MPa to form a multi-layer superposition of the electrode end surface layer blank, the transition layer blank and the electrode base blank. After compaction, the thicknesses of the electrode base, the transition layer and the electrode end surface layer are 6 mm, 2 mm and 1 mm, respectively.

[0053] After the multi-layer blank is pressed, overall hot-pressing sintering is performed under argon protection to generate a multi-layer electrode base. The sintering temperature is 900°C, the pressing load is 120 MPa, the sintering time is 60 min, and after sintering is completed, the furnace is kept at 650°C for heat preservation.

[0054] S3, reverse extrusion forming: The hot-pressing sintered multi-layer electrode base and the hot-pressing mold are taken out of the hot-pressing sintering furnace, the hot-pressing mold ram is replaced with a reverse extrusion mold ram, and the reverse extrusion forming is performed in a press machine. The reverse extrusion forming temperature is 650°C, and the pressing rate is 0.1 mm / s. After reverse extrusion forming, the electrode cap has an outer diameter of 20 mm and a total height of 15 mm. After finishing, the composite spot welding size required composite electrode material is obtained.

[0055] Table 1 is the aluminum alloy resistance spot welding high-conductivity wear-resistant anti-sticking composite electrode material and performance index prepared in examples 1-5. Compared with the conventional chromium-zirconium-copper spot welding electrode, the end face hardness and anti-sticking corrosion resistance of the composite electrode prepared by the application are obviously increased, the wear resistance is increased by 30%, the electrical conductivity is increased by about 10%, and the continuous spot welding times are increased by more than 35%.

[0056] Table 1

[0057] According to the different performance requirements of different regions in the spot welding electrode, the composition ratio of graphene, tungsten carbide and copper-chromium-zirconium alloy powder is regionally adjusted, hot-pressed and sintered to obtain a composite electrode material with high-conductivity matrix and wear-resistant anti-sticking end face. And there is a transition layer between the matrix and the end face to reduce the thermal stress fatigue caused by the difference in thermal expansion coefficient. Through the reverse extrusion process, the composite electrode material meeting the size requirements of the spot welding electrode is obtained, which can further compact the electrode composite material after hot-pressing and sintering, improve the bonding strength of the interface of the multi-layer composite electrode material, at the same time, through the large deformation of reverse extrusion, the grain size can be refined to improve the strength, and the dispersion distribution state of graphene particles in copper-chromium-zirconium alloy is further improved, the material uniformity and conductivity are improved.

[0058] As shown in Figure 2 , the microstructure between the electrode matrix and the transition layer in the composite electrode material obtained according to the proportioning of example 4 is shown. The interfacial bonding is tight, the transition layer is increased, and the thermal stress concentration problem is improved.

[0059] As shown in Figure 3 , the microstructure between the transition layer and the end face layer in the composite electrode material obtained according to the proportioning of example 4 is shown. The interfacial bonding is tight, the end face increases tungsten carbide and graphene to improve wear resistance and conductivity.

[0060] Note that the above is only the preferred embodiment of the present application and the technical principle applied. Those skilled in the art will understand that the present application is not limited to the specific embodiments described herein, and those skilled in the art can make various obvious changes, readjustments and substitutions without departing from the scope of the present application. Therefore, although the present application has been described in more detail through the above examples, the present application is not limited to the above examples, and can include more other equivalent embodiments without departing from the concept of the present application, and the scope of the present application is determined by the scope of the appended claims.

Claims

1. A method of improving the electrical conductivity and stick prevention of an aluminum alloy resistance spot welding electrode, characterized by, The method comprises the following steps: S1, preparation of electrode material powder: S11, preparation of electrode end face layer material powder P1: The electrode end face layer material powder P1 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder; according to wt.% by mass percentage, the graphene powder is 0.5-1.2%, the tungsten carbide powder is 15-60%, and the balance is copper-chromium-zirconium alloy powder; vacuum ball milling for 2h to obtain the wear-resistant and anti-adhesion electrode end face layer material powder P1; S12, preparation of electrode transition layer material powder P2: The electrode transition layer material powder P2 is mixed from copper-chromium-zirconium alloy powder, graphene powder and tungsten carbide powder; according to wt.% by mass percentage, the graphene powder is 0.2-0.6%, the tungsten carbide powder is 5-20%, and the balance is copper-chromium-zirconium alloy powder; vacuum ball milling for 2h to obtain the electrode transition layer material powder P2; S13, preparation of electrode base material powder P3: The electrode base material powder P3 is mixed from copper-chromium-zirconium alloy powder and graphene powder; according to wt.% by mass percentage, the graphene powder is 0.1-0.2%, and the balance is copper-chromium-zirconium alloy powder; vacuum ball milling for 2h to obtain the high-conductivity electrode base material powder P3; S2, overall hot-pressing sintering: The electrode end face layer material powder P1 is loaded into a hot-pressing mold, 200-600MPa is loaded at room temperature, the powder is vibrationally compacted to form a wear-resistant and anti-adhesion electrode end face layer blank; the upper mold press head is lifted, the electrode transition layer material powder P2 is continuously loaded into the hot-pressing mold, the press head is pressed down, the powder is vibrationally compacted at 200-600MPa to form a superposition of the electrode end face layer blank and the transition layer blank; the upper mold press head is lifted, the electrode base material powder P3 is continuously loaded into the hot-pressing mold, the press head is pressed down, and the powder is vibrationally compacted at 200-600MPa to form a multi-layer superposition of the electrode end face layer blank, the transition layer blank and the electrode base blank; the thickness of the electrode end face layer is 1-2mm, and the thickness of the transition layer is 1-2mm; After the multi-layer blank is pressed together, overall hot-pressing sintering is performed under argon protection to generate a multi-layer electrode base; wherein the sintering temperature is 850-1050℃, specifically 900℃, the pressurized load is 80-150MPa, specifically 120MPa, the sintering time is 60-120min, specifically 60min, and after sintering is completed, the furnace is kept at 400-650℃, specifically 650℃; S3, reverse extrusion forming: The hot-pressing sintered multi-layer electrode base and the hot-pressing mold are taken out of the hot-pressing sintering furnace, the hot-pressing mold press head is replaced with a reverse extrusion mold press head, and the reverse extrusion forming is performed in a press machine; the reverse extrusion forming temperature is 400-650℃, specifically 650℃, the pressing rate is 0.05mm / s-2mm / s, specifically 0.1mm / s, the outer diameter of the electrode cap after reverse extrusion forming is 20mm, and the total height is 15mm; after finishing, the composite spot welding size required composite electrode material is obtained; wherein in the hot-pressing sintering and reverse extrusion deformation processes, a mold design of one mold with multiple pieces is adopted.

2. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1, wherein: Step S11, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, the particle size of the graphene powder is less than 0.1 um, and the particle size of the tungsten carbide powder is less than 10 um.

3. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1, wherein: Step S12, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, the particle size of the graphene powder is less than 0.1 um, and the particle size of the tungsten carbide powder is 10 um.

4. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1, wherein: Step S13, the powder particle size of the copper-chromium-zirconium alloy powder is 20-50 um, and the particle size of the graphene powder is less than 0.1 um.

5. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1, wherein: Step S2, load 300 MPa load at room temperature, and vibrate and compact the powder at 200-600 MPa.

6. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1, wherein: Step S2, after compaction, the thicknesses of the electrode base, the transition layer and the electrode end surface layer are 6 mm, 2 mm and 1 mm respectively.

7. The method of improving the electrical conductivity and stick resistance of aluminum alloy resistance spot welding electrodes of claim 1 wherein: Step S2, the sintering temperature is 900 DEG C, the pressure load is 120 MPa, the sintering time is specifically 60 min, and the furnace is kept at 650 DEG C after sintering is completed.

Citation Information

Patent Citations

  • Preparation method for particle reinforced copper-TiC high-intensity high-conductivity spot-welding electrode

    CN102909375A

  • Electrode for resistance spot welding of galvanized steel sheet and preparation method thereof

    CN106181118A

  • Composite tool electrode obtained through hot-pressing sintering of electric spark machine and preparation method

    CN108950145A

  • Graphene tungsten copper alloy modified electrode of gas discharge tube and preparation method

    CN116190179A

  • Method for improving wear resistance of aluminum alloy resistance spot welding electrode

    CN116900434A